Energy regulation for a torque-driven vertical inertia wheel pendulum. (October 2021) - Sandoval, Jesús; Moyrón, Jerónimo; Kelly, Rafael; Santibáñez, Víctor; Moreno-Valenzuela, Javier
Abstract: The energy regulation of a torque–driven vertical inertia wheel pendulum is addressed in this paper, which allows to achieve an oscillatory motion of the non actuated pendulum around its upright position through the proper motion of the actuated inertia wheel. The contribution of the present paper is an energy regulator capable of inducing oscillations of the pendulum with a user specified desired amplitude. More precisely, the proposed controller achieves locally asymptotically an oscillatory motion of pendulum around its upright position, in which its amplitude can be specified within an interval. Simulation and experimental results on a torque–driven inertia wheel pendulum illustrate the performance of the proposed controller.